Top 30 cm soil C org stocks, isotopic C org signature (13dC) and fine sediment content (silt and clay %) estimated in soil cores sampled in seagrass meadows around Australia [dataset] - Mazarrasa, Inés (2020)
This database contains data on top 30 cm soil biogeochemical properties from soil cores (minimum length of 30 cm) sampled in seagrass (n=201 cores) and adjacent unvegetated patches (n=39) around Australia. Average biogeochemical properties per core along with information about type of environment, biotic characteristics and environmental conditions.